POLA AKTIVITAS PENGUNJUNG DALAM PENGGUNAAN RUANG PUBLIK DI STASIUN TAWANG, KOTA SEMARANG SAAT PANDEMI COVID-19 - Ayla Mahrensha (KBK Peracangan Arsitektur dan Kota Program Studi Arsitektur Fakultas Pendidikan Teknologi, 2022)
Public space is a social place where people can carry out various activities in it. In the public space, it will be seen how behavior forms space, and vice versa, space can shape behavior. People's behavior will adjust to conditions during the COVID-19 pandemic. People are required to maintain physical distance and minimize touch. Tawang Station is one of the public spaces that continues to run normally during the pandemic, so that visitors have high mobility and have a high risk of Covid-19 transmission. This study aims to see the behavior of visitors to Tawang Station using behavior mapping analysis techniques. It was found that the movement and activities of visitors at the time of train departure tend to be process activities, where the spaces that accommodate process activities are the lobby, the left waiting room, and the inner waiting room. Meanwhile, the movement and activity upon arrival of the train is a process activity that is accommodated by the right waiting room. So it is found that each space will be crowded with visitors only at certain hours and certain activities. So the policy that can be done by the manager is to limit the number of visitors to Tawang Station and make technological innovations so that activities can be carried out touchless. Keywords: Public Space, Rail Station, Visitor Activities, Beaviour Mapping